Novel insights into the effects of diabetes on gastric motility. (3rd May 2016) - Marathe, Chinmay S.; Rayner, Christopher K.; Jones, Karen L.; Horowitz, Michael
ABSTRACT: Recent data from the Diabetes Control and Complications Trial/Epidemiology of Diabetic Interventions and Complications cohort indicate that the disease burden of gastroparesis in diabetes remains high, consistent with the outcome of cross-sectional studies in type 1 and 2 diabetes. An improved understanding of the pathogenesis of diabetic gastroparesis at the cellular level has emerged in the last decade, particularly as a result of initiatives such as the National Institute of Health funded Gastroparesis Clinical Research Consortium in the US. Management of diabetic gastroparesis involves dietary and psychological support, attention to glycaemic control, and the use of prokinetic agents. Given that the relationship between upper gastrointestinal symptoms and the rate of gastric emptying is weak, therapies targeted specifically at symptoms, such as nausea or pain, are important. The relationship between gastric emptying and postprandial glycaemia is complex and inter-dependent. Short-acting glucagon-like peptide-1 agonists, that slow gastric emptying, can be used to reduce postprandial glycaemic excursions and, in combination with basal insulin, result in substantial reductions in glycated haemoglobin in type 2 patients.